PUBLIC TRUST CONSTRUCTION AND AUDIENCE RECEPTION OF PUBLIC SOLIDARITY MOBILIZATION BY FERRY IRWANDI DURING THE 2025 SUMATRA FLOOD DISASTER ON X - Safira Putri Miranti; Ari Armawan; Dandy Affandy Purba; Rahmanita Ginting (Program Pascasarjana UIN Sumatera Utara, 2026)
The 2025 Sumatra Flood disaster triggered a rapid mobilization of public solidarity in media X and demonstrated how public trust was built through digital communication practices. This study aims to analyze the construction of public trust and audience reception of the mobilization of public solidarity mobilized by Ferry Irwandi as a non-state actor. A qualitative approach with a case study design was used within a constructivist paradigm. Primary data were collected from public conversations in media X using Brand24, covering posts, comments, and netizen interactions from the initial phase of the disaster to the peak of mobilization. Data were analyzed through an integration of Krippendorff's qualitative content analysis with Robert N. Entman's framing theory to map problem definitions, diagnose causes, moral judgments, and treatment recommendations, and Stuart Hall's audience reception theory to read dominant hegemonic positions, negotiations, and opposition. The findings show that the framing in media X frames the disaster as a humanitarian crisis that demands a rapid response, highlights bureaucracy as an obstacle, and positions Ferry Irwandi as a responsive and credible figure, so that direct public participation through donations is understood as the most effective solution. Audience reception reveals a multi-layered spectrum of acceptance, where support and advocacy reproduce the symbolic legitimacy of non-state actors, neutrality reflects contextual evaluation, and criticism serves as a public testing mechanism that reinforces moral standards of solidarity. This study confirms that public trust in disaster situations is formed through the relationship between the visibility of actions, the structure of meaning frames, and audience negotiation in the digital public sphere.